New Headway. Elementary Workbook with key - Soars L. John (New York, Oxford University Press, 2006)
Elementary The world's most trusted English course New Headways the course teachers and learners can rely on. Why? An authoritative integrated syllabus, motivating topics, and clearly focused tasks combine with a real understanding of what works in the classroom. It all makes for effective teaching and effective learning.Tried and tested all over the world, it's probably the most popular course ever written what's in of New Headway Elementary Workbook? Thorough practice of the Student's Book grammar syllabus Revision of key vocabulary and functions 100% new reading texts New translation section Listening and pronunciation exercises for self-study ... attractive, well-organised,and easy to use.